Adjustment and maladjustment to later life: Evidence about early experiences in the family - Alcaide, Marta; Garcia, Oscar F.; Queiroz, Pablo; Garcia, Fernando (Frontiers in Psychology, 2023)
Previous parenting studies with European-American families have identified optimal parenting as being based on warmth combined with strictness (i.e., authoritative parenting). The present study analyzes, in adolescents and adults, their adjustment and maladjustment related to age and their early experiences in the family. The sample consisted of 2,158 Spanish people (58.29% women): 624 adolescents, 630 young adults, 504 middle-aged adults, and 400 older adults. The families were classified into one of the four parental typologies (authoritative, indulgent, authoritarian, and neglectful) based on their scores in the two main dimensions (warmth and strictness). Child functioning was measured as components of adjustment (self-esteem, emotional self-concept, and empathy) and maladjustment (aggression and hostile sexism). Overall, only adolescents and adult children raised in indulgent families reported the highest self-esteem, emotional self-concept, and empathy, and the lowest aggression and hostile sexism. Authoritative parenting (warmth with strictness) was related to a lower emotional self-concept and greater aggression and hostile sexism than indulgent parenting (warmth without strictness). The worst scores corresponded to authoritarian and neglectful parenting. The present findings provide new evidence about early experiences in the family, even after parental socialization has ended. Interestingly, contrary to the main findings from classic studies with European-American families, only high parental warmth combined with low parental strictness (i.e., indulgent parenting) is always positive for greater adjustment and less maladjustment in all age groups.